An improved method for the harmonic contributions assessment of utility and customer in distribution systems: part A analytical study - Fadl, Omar F.; Eisa, Ayman A.; Adail, Ahmed S.; Osman, Elsaid A. (International Journal of Engineering and Technology, 2018)
A new method is proposed to find suitable definitions of electrical power components in non-sinusoidal conditions, which based on the analysis of three-phase instantaneous power flows of both fundamental and all harmonics of signals in three-phase non-sinusoidal system. This paper also introduces an attempt to get the physical essence of the proposed three-phase power components for any non-sinusoidal unbalanced three-phase system. Therefore, we can use the formulas of these definitions with modern digital measurement technology in order to reach to revenue meter which enables us to identify the responsible for the harmonic distortion between customers and distribution utilities. The aim of this paper is presenting an analytical study that will rely on it in the next paper part B, in order to assess the contributions of harmonic distortion for utility and the customer at the Point of Common Coupling (PCC).